Levels of human immunodeficiency virus type 1-specific cytotoxic T-lymphocyte effector and memory responses decline after suppression of viremia with highly active antiretroviral therapy. - Kalams, SA; Goulder, P; Shea, A; Jones, N; Trocha, A; Ogg, G; Walker, B (1999)
Therapeutic suppression of human immunodeficiency virus type 1 (HIV-1) replication may help elucidate interactions between the host cellular immune responses and HIV-1 infection. We performed a detailed longitudinal evaluation of two subjects before and after the start of highly active antiretroviral therapy (HAART). Both subjects had evidence of in vivo-activated and memory cytotoxic T-lymphocyte precursor (CTLp) activity against multiple HIV-1 gene products. After the start of therapy, both subjects had declines in the levels of in vivo-activated HIV-1-specific CTLs and had immediate increases in circulating HIV-1-specific CTL memory cells. With continued therapy, and continued suppression of viral load, levels of memory CTLps declined. HLA A*0201 peptide tetramer staining demonstrated that declining levels of in vivo-activated CTL activity were associated with a decrease in the expression of the CD38(+) activation marker. Transient increases in viral load during continued therapy were associated with increases in the levels of virus-specific CTLps in both individuals. The results were confirmed by measuring CTL responses to discrete optimal epitopes. These studies illustrate the dynamic equilibrium between the host immune response and levels of viral antigen burden and suggest that efforts to augment HIV-1-specific immune responses in subjects on HAART may decrease the incidence of virologic relapse.